A comparative study of phytoplankton community structure and biomass determined by HPLC-CHEMTAX and microscopic methods during summer and autumn in the central Bohai Sea, China. (June 2020) - Pan, Huizhu; Li, Aifang; Cui, Zhengguo; Ding, Dongsheng; Qu, Keming; Zheng, Yaoyang; Lu, Lin; Jiang, Tao; Jiang, Tianjiu
Abstract: As the largest inland sea of China, the Bohai Sea has confronted significant environmental changes in recent decades, and a shift of phytoplankton community from diatoms to dinoflagellates was observed by microscopic method in previous studies. However, the counting of some small-sized non-diatoms (e.g., flagellates and cyanobacteria) have long been neglected due to the limitation of this method. In this study, we measured the phytoplankton community structure and abundance in the central Bohai Sea in summer and autumn of 2015 by employing both microscopic method and high-performance liquid chromatography (HPLC) pigments – CHEMTAX analysis. The results of microscopic counting showed that the phytoplankton community was characterized by diatoms, dinoflagellates, and chrysophytes, which contained a total of 107 species. Dinoflagellates and diatoms co-dominated in summer while the latter became the dominant group in autumn. Compared with microscopic counting, CHEMTAX analysis allowed identification of a larger number of phytoplankton groups (including 8 phyla). The results of CHEMTAX analysis showed that besides diatoms and dinoflagellates, the small-sized non-diatoms (i.e., flagellates and cyanobacteria) also played an important role. Diatoms and cyanobacteria dominated the total Chl a (contributing 32.5% and 17.1%, respectively), followed by cryptophytes, dinoflagellates, and prasinophytes in the summer. A short-term summer to autumn variability of phytoplankton abundance and community was observed. Temperature and nutrient availability affected the succession of the phytoplankton community from diatoms and non-diatoms co-dominance in the summer to absolute diatoms dominance in the autumn. A direct comparison of algal cell abundance and CHEMTAX biomass showed that a significant positive correlation was observed only for dinoflagellates ( P < 0.01) in the autumn. Our work provides some basic information on the dynamics of small-sized flagellates and cyanobacteria in this area, and also suggests that a combination of both the methods is needed in future investigations to better understand the current status as well as the future changes of phytoplankton community. Highlights: Microscopic analysis showed diatoms, dinoflagellates and chrysophytes in seawater. CHEMTAX analysis allowed identification of a larger number of phytoplankton groups. Variation of phytoplankton community from summer to autumn was observed. Temperature and nutrients affected the variation of the phytoplankton community.